2004
DOI: 10.1002/cncr.20623
|View full text |Cite
|
Sign up to set email alerts
|

Is routine triple endoscopy for head and neck carcinoma patients necessary in light of a negative chest computed tomography scan?

Abstract: BACKGROUND The objective of the current study was to analyze the results obtained by triple endoscopy during the initial evaluation of a primary carcinoma of the head and neck. METHODS A total of 487 patients with a squamous cell carcinoma of the head and neck was studied. None of the patients had evidence of metastasis or a second primary tumor on the thoracic computed tomography (CT) scan or chest X‐ray. All patients underwent a triple endoscopy including nasopharyngoscopy, laryngoscopy, pharyngoscopy, bronc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
38
0
6

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(48 citation statements)
references
References 29 publications
1
38
0
6
Order By: Relevance
“…In our study, we found that laryngeal and hypopharyngeal primary SCCs had a significantly higher rate of lung SPMs than other HNSCCs, and that hypopharyngeal primary SCCs had a higher rate of esophageal SPMs. This is consistent with previous studies, some of which have noted higher rates of lung SPMs after laryngeal primary diagnosis, as well as the potential benefit of esophagoscopy for SPM in hypopharyngeal cancers [11,17]. …”
Section: Discussionsupporting
confidence: 93%
“…In our study, we found that laryngeal and hypopharyngeal primary SCCs had a significantly higher rate of lung SPMs than other HNSCCs, and that hypopharyngeal primary SCCs had a higher rate of esophageal SPMs. This is consistent with previous studies, some of which have noted higher rates of lung SPMs after laryngeal primary diagnosis, as well as the potential benefit of esophagoscopy for SPM in hypopharyngeal cancers [11,17]. …”
Section: Discussionsupporting
confidence: 93%
“…However, huge diversity exists between the reported incidences for synchronous and metachronous esophageal cancers. With such inconclusive results, some researchers have questioned the efficacy and cost-benefit of the routine use of panendoscopy to detect synchronous and metachronous esophageal cancers [6][9].…”
Section: Introductionmentioning
confidence: 99%
“…3,18 Therefore, some diagnostic strategies regarding the evaluation of hypopharyngeal cancer are suggested in clinical practice, such as selective screening in patients with significant dysphagia and routine screening of esophageal cancer through barium esophagogram or gastroscopy. 19,20 In this study, unsedated transnasal EGD was able to detect and pathologically diagnose simultaneous invasive esophageal cancer in 6 patients (22.2%), 2 of whom had small T1 lesions that had no associated symptoms and may be missed by barium esophagogram. The treatment plans of these 6 patients were all changed for these simultaneous cancers.…”
Section: Discussionmentioning
confidence: 92%